(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Castellated beam applications for diverse buildings are quickly gaining popularity. This is a result of the section’s enhanced depth without adding weight, excellent strength-to-weight ratio, low maintenance requirements, and low cost of painting. Increased vertical bending stiffness, ease of service provision, and appealing appearance are the main advantages of castellated beams. Castellated beams are made by zigzaggingly cutting I sections, then rejoining them to increase the depth of the parent I sections. When castellated beams are loaded, their increased depth makes them more susceptible to web post buckling and lateral torsional buckling failure. There are numerous other forms of failure that must be considered, such as the development of flexure mechanisms, lateral torsional buckling, and vierendeel mechanisms, rupture of the welded joint in a web post, and shear buckling of a web post. A study demonstrates how using stiffeners in the beam’s web part can reduce these failures. Therefore, it is necessary to do a thorough analysis of the stiffeners’ number, size, and readily available places in the web part of the castellated beam. In order to explore the experimental and analytical behavior of the castellated beam with stiffeners, an attempt has been undertaken in the current paper. The outcome shows that using end stiffeners at the ends of castellated beams increases their strength and reduces their deflection.